IMPLEMENTASI PROGRAM AREA TRAFFIC CONTROL SYSTEM (ATCS) DALAM KETERTIBAN BERLALU LINTAS DI KOTA MEDAN - Tesya Margaretta Silaban; Siti Hazzah Nur. R. (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: The Area Traffic Control System (ATCS) program is a combination of Closed Circuit Television (CCTV) systems and traffic light control at several points that function as traffic data centers that are useful for recording, controlling traffic, and knowing quickly in the field related to public order. in traffic. The purpose of the study was to determine and describe the implementation of the ATCS program policy in traffic order in the city of Medan. The form of research is qualitative with data collection methods, namely interviews, observations, and documentation. The results of this study are the implementation of the ATCS program policy in traffic order in the city of Medan has not been maximized because there are still obstacles experienced.Keywords: implementation; area traffic control system (ATCS) program; orderAbstrak: Program Area Traffic Control System (ATCS) adalah gabungan sistem Closed Circuit Television (CCTV) dan kontrol lampu lalu lintas di sejumlah titik yang berfungsi sebagai pusat data lalu lintas yang berguna merekam, mengontrol lalu lintas, hingga mengetahui secara cepat di lapangan terkait dengan ketertiban masyarakat dalam berlalu lintas. Tujuan penelitian untuk mengetahui dan mendeskripsikan implementasikebijakan program ATCS dalam ketertiban berlalu lintas di Kota Medan. Bentuk penelitian adalah kualitatif dengan metode pengumpulan data yaitu wawancara, observasi dan dokumentasi. Hasil penelitian ini adalah implementasi kebijakan program ATCS dalam ketertiban berlalu lintas di Kota Medan belum maksimal karena masih terdapat kendala- kendala dialami.Kata kunci: implementasi; program area traffic control system (ATCS); ketertiban